Effect of perphenazine and prochlorperazine on viability of human astrocytes - Michał Otręba; Anna Rzepecka-Stojko; Jerzy Stojko; Agata Kabała-Dzik; Anna Kleczka (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Phenothiazine derivatives are well-known anti-psychotic drugs that possess several biological activities including anticancer activity. Much research provides data about its anticancer activity against human glioblastoma cell lines. Unfortunately, to date in vitro studies analyzing the impact of phenothiazines on the viability of human astrocytes have not been performed. However, it is possible to find one study about the viability of neurons and neurons with glia after incubation with perphenazine. Thus, in this study we measured the viability of human astrocytes after 24-, 48-, and 72-hour incubation with perphenazine and prochlorperazine dimaleate using the WST-1 assay. The obtained results suggest that perphenazine is safer for human astrocytes than prochlorperazine dimaleate. Moreover, 24-hour incubation with perphenazine or prochlorperazine did not significantly reduce cellular viability. It is a very important finding since previously we proved that in similar concentrations both drugs reduce the viability of the human glioblastoma U-87 MG cell line by approximately 50%. Therefore, the results suggest that phenothiazines can be used in glioblastoma treatment in concentrations that do not impact human astrocyte viability.